The time structure of Cherenkov images generated by TeV γ-rays and by cosmic rays - Heß, Maximilian; Bernlöhr, Konrad; Daum, A.; Hemberger, M.; Hermann, G.; Hofmann, W.; Lampeitl, H.; Aharonian, F. A.; Akhperjanian, A. G.; Barrio, J. A.; Beteta, J. J. G.; Contreras, J. L.; et al. (Astroparticle physics, 1999)
The time profiles of Cherenkov images of cosmic-ray showers and of γ-rays showers are investigated, using data gathered with the HEGRA system of imaging atmospheric Cherenkov telescopes during the 1997 outbursts of Mrk 501. Photon arrival times are shown to vary across the shower images. The dominant feature is a time gradient along the major axis of the images. The gradient varies with the distance between the telescope and the shower core, and is maximal for large distances. The time profiles of cosmic-ray showers and of γ-ray showers differ in a characteristic fashion. The main features of the time profiles can be understood in terms of simple geometrical models. Use of the timing information towards improved shower reconstruction and cosmic-ray supperssion is discussed.
Gesehen am 18.11.2020